Integrating Local Wisdom and Waqf Regulation: Toward an Inclusive Governance Model of Indigenous Land-Waqf in Indonesia and India - Salmawati Salmawati; Muh. Zulkifli Muhdar; Uzodinma Yurriens Ezenduka (Fiat Justisia: Jurnal Ilmu Hukum, 2026)
The integration of local wisdom and waqf practices is a critical issue in the legal and social development of multicultural countries such as Indonesia and India, where Islamic law, state law, and customary law often overlap, creating legal uncertainty, particularly for communal waqf land. Using a normative legal method with statutory and comparative approaches, this study finds that both countries practice legal pluralism: Indonesia excels in formal mechanisms through land certification and communal nadzir, while India demonstrates institutional robustness via the State Waqf Board. Building on these insights, the study proposes a dual-legitimacy governance model that integrates Islamic law, state regulations, and customary norms, emphasizing inclusive governance, customary-based mediation, and distributive justice to ensure both the sustainability of waqf assets and the welfare of indigenous communities.